Petrology of Rapti River sand, Hetauda-Chitwan Dun Basin, Central Nepal; an example of recycled provenance - Tamrakar, Naresh Kazi; Maharjan, Surendra; Shrestha, Madhusudan Bhakta (Bulletin of the Department of Geology, 2008)
The Rapti River in the Central Nepal drains fold-thrust belts of the Lesser and the Sub-Himalayas as demarcated by four major thrusts, and is located in humid sub-tropical climatic zone. Within the Sub-Himalaya (Siwalik Group), a wide Dun Valley gives way the long low-gradient Rapti River in the northeast region, therefore, forming a characteristic piggy-back basin within the foldthrust belts. Sands from the Rapti River were obtained and analysed to characterise composition and texture, to verify its provenance, and to compare with modern and ancient sands/sandstones from different basins having similar tectonic setting. The Rapti River sand is quarto-lithic in composition. It plots on recycled orogeny provenance field in the QFL and QmFLt triangle diagrams showing no major difference in provenance with other sands/ sandstones from different climates. However, the Rapti River sand is remarkably poorer in feldspar but richer in lithic fragments and quartz compared to the other sands/sandstones. doi: 10.3126/bdg.v11i0.1539 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 23-30